ANALISIS HUBUNGAN KUALITAS SUMBER DAYA MANUSIA PEGAWAI DENGAN KINERJA LAYANAN PUSAT PRESTASI NASIONAL DI ERA REVOLUSI INDUSTRI 4.0 - Topanal Gustiranda; Tatan Sukwika; Harsono Hadisumarjo (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Puspresnas as an institution that always strives to provide technical assistance and optimal expertise to to the Minister of Education, Culture, Research, and Technology. The picture of the future that is the goal of Puspresnas is the realization of excellent and maximum service to students and educational units throughout Indonesia. The era of the industrial revolution 4.0 requires human resources who are able to adapt and are competent in the use of technology in the office. This study aims to analyze the correlation between competence, adaptation, and skills of the employees’ service performance. This study uses a quantitative approach with data collection methods using questionnaires to Puspresnas employees. The results show that the coefficient value for the constant is not significant, and the constant values of the Competence, Adaptation, and Skills variables are 0.416, 0.354, and 0.224, respectively. The regression equation for service performance above shows that the three independent variables have a positive impact on employee service performance. From the results of the analysis, the increase in competence, adaptation, and skills have an effect on improving employee service performance. The results of the study stated that the competence, adaptation and skills of employees were closely related to the service performance of employees at Puspresnas in the Industrial Revolution 4.0 era. In the transformation of change to an all-digital era, it is necessary to periodically train employees so that they can adjust their skills with increasingly rapid technological developments.